Global cardiac risk assessment in the Registry Of Pregnancy And Cardiac disease: results of a registry from the European Society of Cardiology. (22nd March 2016) - van Hagen, Iris M.; Boersma, Eric; Johnson, Mark R.; Thorne, Sara A.; Parsonage, William A.; Escribano Subías, Pilar; Leśniak‐Sobelga, Agata; Irtyuga, Olga; Sorour, Khaled A.; Taha, Nasser; Maggioni, Aldo P.; Hall, Roger; et al.
Abstract: Aims: To validate the modified World Health Organization (mWHO) risk classification in advanced and emerging countries, and to identify additional risk factors for cardiac events during pregnancy. Methods and results: The ongoing prospective worldwide Registry Of Pregnancy And Cardiac disease (ROPAC) included 2742 pregnant women (mean age ± standard deviation, 29.2 ± 5.5 years) with established cardiac disease: 1827 from advanced countries and 915 from emerging countries. In patients from advanced countries, congenital heart disease was the most prevalent diagnosis (70%) while in emerging countries valvular heart disease was more common (55%). A cardiac event occurred in 566 patients (20.6%) during pregnancy: 234 (12.8%) in advanced countries and 332 (36.3%) in emerging countries. The mWHO classification had a moderate performance to discriminate between women with and without cardiac events (c‐statistic 0.711 and 95% confidence interval (CI) 0.686–0.735). However, its performance in advanced countries (0.726) was better than in emerging countries (0.633). The best performance was found in patients with acquired heart disease from developed countries (0.712). Pre‐pregnancy signs of heart failure and, in advanced countries, atrial fibrillation and no previous cardiac intervention added prognostic value to the mWHO classification, with a c‐statistic of 0.751 (95% CI 0.715–0.786) in advanced countries and of 0.724 (95% CI 0.691–0.758) in emerging countries. Conclusion: The mWHO risk classification is a useful tool for predicting cardiac events during pregnancy in women with established cardiac disease in advanced countries, but seems less effective in emerging countries. Data on pre‐pregnancy cardiac condition including signs of heart failure and atrial fibrillation, may help to improve preconception counselling in advanced and emerging countries.